Spatial resolution of neutron radiography system by Nomte Carlo simulation - Wan Hassan, Wan Muhamad Saridan; Marto, Sumilah; Kasmin, Khalid; Muhamad, Azali (Faculty of Science, University Teknologi Malaysia, 2007)
A simulation of neutron imaging was performed to investigate the spatial resolution propertiesof a neutron radiography system. A cadmium plate was imaged by neutrons using a planeradiographic detector placed behind the plate. The detector was evoked by the radiographictally facility of a Monte Carlo simulation codes. Radiograph of the cadmium plate wasobtained and the edge spread function data were extracted from it. Modulation transferfunction which gives the spatial resolution properties was calculated from the edge spreadfunction data